2012
DOI: 10.5625/lar.2012.28.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract ofLiriope platyphylla, a traditional Chinese medicine, significantly inhibits abdominal fat accumulation and improves glucose regulation in OLETF type II diabetes model rats

Abstract: Liriope platyphylla is a medical herb that has long been used in Korea and China to treat cough, sputum, neurodegenerative disorders, obesity, and diabetes. The aims of this study were to determine the antidiabetic and antiobesity effects of aqueous extract of L. platyphylla (AEtLP) through glucose and lipid regulation in both pre-diabetes and obesity stage of type II diabetes model. Two concentrations of AEtLP were orally administrated to OLETF (Otsuka Long-Evans Tokushima Fatty) rats once a day for 2 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…AEtLP to ICR mice displayed a significant reduction of the glucose and increased insulin concentrations [37]. Significant alterations on serum adiponectin and lipid concentration [35,36] with GLUT-3, GLUT-1, JNK, and p38 pathway [35] and SOD expressions [37] were also reported. The insulin level was dramatically elevated upon co-treatment with high glucose and AEtLP in INS-1 cells may be tightly correlated with calcium regulation [38,39].…”
Section: Anti-diabetic Anti-lipidemic and Insulin Sensitizer Activimentioning
confidence: 86%
See 1 more Smart Citation
“…AEtLP to ICR mice displayed a significant reduction of the glucose and increased insulin concentrations [37]. Significant alterations on serum adiponectin and lipid concentration [35,36] with GLUT-3, GLUT-1, JNK, and p38 pathway [35] and SOD expressions [37] were also reported. The insulin level was dramatically elevated upon co-treatment with high glucose and AEtLP in INS-1 cells may be tightly correlated with calcium regulation [38,39].…”
Section: Anti-diabetic Anti-lipidemic and Insulin Sensitizer Activimentioning
confidence: 86%
“…In addition, it inhibits glycogen synthase kinase-3 (GSK-3) expression and increases IR, IRS-1, PI3K, protein kinase B (Akt), and glucose transport protein (GLUT)-4 expressions in the liver [34]. AEtLP dramatically decreased the abdominal fat mass and slightly decreased the glucose concentration [35], although no significant differences in body weight, glucose tolerance, and glucose concentration [36] in Otsuka Long-Evans Tokushima Fatty (OLETF) rats. AEtLP to ICR mice displayed a significant reduction of the glucose and increased insulin concentrations [37].…”
Section: Anti-diabetic Anti-lipidemic and Insulin Sensitizer Activimentioning
confidence: 99%
“…Next, 600 g of dry roots were reduced to powder using an electric blender, then extracted in 2 L of distilled water, after which the water extract was purified at 100℃ for 2 h using circulating extraction equipment (IKA Labortechnik, Staufen, Germany). The calories and main composition of AEtLP were measured in previous studies [ 15 16 ]. Extract solutions were concentrated into dry pellets using a rotary evaporator (EYELA, Tokyo, Japan), then stored at -80℃ until use.…”
Section: Methodsmentioning
confidence: 99%
“…A root tuber of L. platyphylla has been proven the efficacy of anti-inflammatory, anti-asthmatic effects (Lee et al 2005). It is also reported that aqueous extract of L. platyphylla has been shown to be effective in type 2 diabetes mellitus (Kim et al 2012). These effects come from many bioactive substances contained in their tuber.…”
Section: Liriope Platyphylla; Chloroplast Genome; Phylogenetic Analysismentioning
confidence: 99%